2015
DOI: 10.5194/bg-12-3499-2015
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of metal ion homeostasis in soils is associated with nitrogen deposition-induced species loss in an Inner Mongolia steppe

Abstract: Abstract. Enhanced deposition of atmospheric nitrogen (N) resulting from anthropogenic activities has negative impacts on plant diversity in ecosystems. Several mechanisms have been proposed to explain the species loss. Ion toxicity due to N deposition-induced soil acidification has been suggested to be responsible for species loss in acidic grasslands, while few studies have evaluated the role of soil-mediated homeostasis of ions in species loss under elevated N deposition in grasslands with neutral or alkali… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 56 publications
2
29
0
Order By: Relevance
“…5d, e, f) suggested accumulation of available Fe relative to Mn under soil acidification as affected by enhanced N inputs. Consistent with our findings, Tian et al (2015Tian et al ( , 2016 found soil acidification enhanced Mn uptake and reduced Fe absorption by forbs which result in lower photosynthetic rates and growth and loss of forb species. Plant Fe deficiency was reported to induce chlorosis and decrease photosynthesis in calcareous grassland (Rogovska et al, 2007).…”
Section: The Stoichiometric Ratios Among Different Soil Aggregates Frsupporting
confidence: 93%
“…5d, e, f) suggested accumulation of available Fe relative to Mn under soil acidification as affected by enhanced N inputs. Consistent with our findings, Tian et al (2015Tian et al ( , 2016 found soil acidification enhanced Mn uptake and reduced Fe absorption by forbs which result in lower photosynthetic rates and growth and loss of forb species. Plant Fe deficiency was reported to induce chlorosis and decrease photosynthesis in calcareous grassland (Rogovska et al, 2007).…”
Section: The Stoichiometric Ratios Among Different Soil Aggregates Frsupporting
confidence: 93%
“…High atmospheric sulfur deposition (dry and wet) is also predicted to continue in the short term in these regions, despite stricter regulation of sulfur dioxide emissions being implemented in recent years (Pan et al, 2013;Zhang et al, 2012;Zhao, 2009;Hijmans et al, 2005). Hence, soil acidification may continue for a long time in northern China (Guo et al, 2010;Lieb et al, 2011), posing a severe ecological threat to these ecosystems (Chen et al, 2013;Tian et al, 2015). For instance, soil acidification changed the belowground communities and soil properties, decreased the plant diversity and productivity, and reduced the community stability (Chen et al, 2013).…”
Section: W T Luo Et Al: Ph Buffering In Neutral-alkaline Soilsmentioning
confidence: 99%
“…For instance, soil acidification changed the belowground communities and soil properties, decreased the plant diversity and productivity, and reduced the community stability (Chen et al, 2013). The soil acidification induced by N addition resulted in the disruption of metal ion homeostasis in soils and hence species loss (Tian et al, 2015). Nonetheless, there has been no comprehensive assessment of the extent, trends and mechanisms of soil pH decline in response to acid deposition across these ecosystems.…”
Section: W T Luo Et Al: Ph Buffering In Neutral-alkaline Soilsmentioning
confidence: 99%
See 2 more Smart Citations